A tabu search approach to the jump number problem - Krysztowiak, P.; Sysło, M.M. (Algebra and Discrete Mathematics, 2015)
We consider algorithmics for the jump number problem, which is to generate a linear extension of a given poset, minimizing the number of incomparable adjacent pairs. Since this problem is NP-hard on interval orders and open on two-dimensional posets, approximation algorithms or fast exact algorithms are in demand. In this paper, succeeding from the work of the second named author on semi-strongly greedy linear extensions, we develop a metaheuristic algorithm to approximate the jump number with the tabu search paradigm. To benchmark the proposed procedure, we infer from the previous work of Mitas [Order 8 (1991), 115--132] a new fast exact algorithm for the case of interval orders, and from the results of Ceroi [Order 20 (2003), 1--11] a lower bound for the jump number of two-dimensional posets. Moreover, by other techniques we prove an approximation ratio of n/ log(log(n)) for 2D orders.